Thinking of work as an educational principle and non-formal education as bases for omnilateral education (Research, Society and Development, 2020)
This article aims to revisit the considerations about non-formal education as a basis for the implementation of omnilateral education in the scope of Professional and Technological Education. Work as a constitutive element of being is present in all dimensions of human life. From the practical activity, passing through the intellectual capacity of (re) construction of knowledge, until the definition of the intentionalities, the idealized ends and the real results. In this sense, it structures man in his entirety, configuring himself as a principle that underlies the educational process – outlining man as a being who learns to be, through the processes of consciousness, and to produce, in his ontological dimension, for a certain purpose. Professional and technological education, in the context of the implementation of integrated high school, apprehends the work in this ontological perspective and thus it is intended to achieve integral human formation. It is suggested, however, to compose the triad, the absorption of the non-formal education modality also as a foundation and basis for and implementation of integrated high school, since they share the same principles of training for citizenship, to build political agents and critics of social reality. This is a literature review, the result of a qualitative and exploratory research, which was a stage carried out within the scope of the Professional Master in Professional and Technological Education - PROFEPT / IFAL, in progress.